Estudo da seletividade de lipases para a obtenção de ésteres de ácidos graxos - Bastos, Ana Karine Pessoa (2013)
Esters of fatty acids represent one of the most important classes of organic compounds due to ther variety of applications, such as flavoring, biopesticide, biodiesel and antimicrobials. Oils and fats industry as well as scientific researches have developed many different processes to manipulate composition of triglycerides mixtures. The aim is synthesis of esters from fatty acids by chemical or enzymatic routes. In this context, lipase is the most widely used enzyme due to several advantages related its specificity. The aim of this study was to evaluate the selectivity of immobilized lipases of Candida antarctica type B and Rhizopus oryzae compared to saturated (SFA) and unsaturated (UFA) fatty acids as well as their yield into ethyl esters. Selectivity was assessed with respect to oleic acid (unsaturated) and eicosanoic acid (saturated), obtained from chemical hydrolysis of fish oil Tilapia (Oreochromis niloticus), through 24 central composite design using agitation rate (rpm), temperature (°C), molar ratio (ethanol:fatty acid) and amount of enzyme (%wt) as independ variables (design factors). The amount of molecular sieve – zeolite 5 Å – (5 %wt) and reaction time (24 h) were fixed. Likewise, the behavior of both enzymes to the SFA was evaluated according to 23 central composite design where temperature (°C), molar ratio (ethanol:fatty acid) and amount of enzyme (%wt) were independ variables. The amount of molecular sieve – zeolite 5 Å – (5 %wt), stirring (180 rpm) and reaction time (24 h) were fixed and a mixture of palmitic and stearic acids was used as substrate. A confidence interval of 85% was considered for all statistical analyses. Regarding the esterification of fatty acids from hydrolyzed fish oil, both catalysts were selective for saturated eicosanoic acid rather than for the unsaturated acid. The design factors did not present significant effect on response variable when lipase from C. antarctica was used like catalyst. However all design factors presented an influence on the selectivity when lipase from R. oryzae was used like catalyst. In this way, lipase of C. antarctica lead to higher conversions of oleic acid into ethyl oleate and more significant variables have been found for the model when lipase of R. oryzae was uesd in assays. In the reaction medium containing the mixture of SFA, both lipases showed higher affinity for palmitic acid. The values range selected to evaluate the selectivity did not present significant effect on responses when lipase from C. antarctica was used, however that value range was significant for all assays performed using lipase from R. oryzae. The higher stearic acid conversions were obtained when lipase from C. antarctica was used like catalyst and all design factors were significant for both enzymes.